‘Toning’ up hypotonia assessment: A proposal and critique - Pragashnie Govender (nee' Naidoo); Robin W.E. Joubert (African Journal of Disability, 2016)
Background: Clinical assessment of hypotonia is challenging due to the subjective nature of the initial clinical evaluation. This poses dilemmas for practitioners in gaining accuracy, given that the presentation of hypotonia can be either a non-threatening or malevolent sign. The research question posed was how clinical assessment can be improved, given the current contentions expressed in the scientific literature.